The Role of PPKN Teachers in Strengthening Anti-Corruption Values in Class X at SMA Negeri 1 Sarolangun - Febriyanti, Wiwit; Amin, Zulkifli (EDUCTUM: Journal Research, 2023)
Where anti-corruption education is a conscious effort to provide understanding and prevention of acts of corruption committed from formal education in schools, informal education in the family environment, and non-formal education in the community. Most people may still think that corruption is only limited to the act of someone taking money that is not rightfully theirs. In fact, corruption can actually arise from various causes and even the place where corruption occurs is not only limited to the political arena. Education is recognized as the easiest and most effective strategy for changing, at least directing one's way of thinking and mindset in acting. Schools occupy a strategic position in implementing anti-corruption education, especially in cultivating anti-corruption behavior among students. Therefore, the researchers conducted this research with the aim of finding out the role of PKN teachers in strengthening anti-corruption values in class X at SMA Negeri 1 Sarolangun in the 2022/2023 academic year, with a total of 36 students. Using quantitative research methods, data collection techniques in this study were observation and questionnaire distribution in class X. Data analysis techniques used in this study were normality tests and hypothesis testing. The results of the analysis show that regarding variable (x) the role of PKN teachers in strengthening anti-corruption values. It can be seen from the significant value of the role of the pkn teacher (x) 0.000 <0.05 but in the value thitung 2,548 > 1.688 (t tabel = 0.05:1.688) So it can be concluded that there is a positive influence and significant between the independent variable and the dependent variable.